Therapeutic targeting of PARP with immunotherapy in acute myeloid leukemia - Bian, Xing; Liu, Wenli; Yang, Kaijin; Sun, Chuanbo (Frontiers in Pharmacology, 2024)
Targeting the poly (ADP-ribose) polymerase (PARP) protein has shown therapeutic efficacy in cancers with homologous recombination (HR) deficiency due to BRCA mutations. Only small fraction of acute myeloid leukemia (AML) cells carry BRCA mutations, hence the antitumor efficacy of PARP inhibitors (PARPi) against this malignancy is predicted to be limited; however, recent preclinical studies have demonstrated that PARPi monotherapy has modest efficacy in AML, while in combination with cytotoxic chemotherapy it has remarkable synergistic antitumor effects. Immunotherapy has revolutionized therapeutics in cancer treatment, and PARPi creates an ideal microenvironment for combination therapy with immunomodulatory agents by promoting tumor mutation burden. In this review, we summarize the role of PARP proteins in DNA damage response (DDR) pathways, and discuss recent preclinical studies using synthetic lethal modalities to treat AML. We also review the immunomodulatory effects of PARPi in AML preclinical models and propose future directions for therapy in AML, including combined targeting of the DDR and tumor immune microenvironment; such combination regimens will likely benefit patients with AML undergoing PARPi-mediated cancer therapy.